2018
DOI: 10.1016/j.ajog.2018.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Receipt of adjuvant endometrial cancer treatment according to race: an NRG Oncology/Gynecologic Oncology Group 210 Study

Abstract: Contrary to our hypothesis, we observed higher odds of specific adjuvant treatment regimens among black women as compared with white women within specific subgroups of endometrial cancer characteristics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 32 publications
1
16
0
Order By: Relevance
“…Our work extends that previous analysis by comparing, for the first time, rates of local and distant recurrence as well as PFS and DFS. The results from our meta-analysis are also consistent with several studies that, drawing on the US National Cancer Database, suggest better survival with ACR than AC [ 18 , 37 , 38 ]. In addition, we found evidence of better survival with ACR than AC specifically in patients with endometrial cancer in stage IIIC.…”
Section: Discussionsupporting
confidence: 91%
“…Our work extends that previous analysis by comparing, for the first time, rates of local and distant recurrence as well as PFS and DFS. The results from our meta-analysis are also consistent with several studies that, drawing on the US National Cancer Database, suggest better survival with ACR than AC [ 18 , 37 , 38 ]. In addition, we found evidence of better survival with ACR than AC specifically in patients with endometrial cancer in stage IIIC.…”
Section: Discussionsupporting
confidence: 91%
“…12), reflecting the higher proportion of Black women diagnosed with nonendometrioid, high‐risk disease. When stratified by disease subtype, receipt of guideline‐concordant therapy in hospital‐based studies was lower among Black women than among White women for endometrioid subtypes, 183 but it was similar for nonendometrioid cancers 184,185 . However, population‐based studies of patients aged 65 years or older have reported that Black patients are more likely than White patients to have treatment delays and are less likely to receive adjuvant therapy regardless of histology 186,187 …”
Section: Selected Findingsmentioning
confidence: 99%
“…When stratified by disease subtype, receipt of guideline-concordant therapy in hospital-based studies was lower among Black women than among White women for endometrioid subtypes, 183 but it was similar for nonendometrioid cancers. 184,185 However, population-based studies of patients aged 65 years or older have reported that Black patients are more likely than White patients to have treatment delays and are less likely to receive adjuvant therapy regardless of histology. 186,187 Uterine corpus cancer is one of the few cancers for which survival has not substantially improved since the mid-1970s, reflecting few advances in treatment.…”
Section: Uterine Corpus (Endometrium)mentioning
confidence: 99%
“…The results from our meta-analysis are consistent with several previous studies. For example, analysis of data in the US National Cancer Data Base suggests better survival with ACR than AC [18,28,42] .…”
Section: Discussionmentioning
confidence: 99%